Regulatory responses by countries to banking/financial crises - James R. Barth (Journal of Risk and Financial Management, 2020)
Banking/financial crises have occurred in countries at all levels of income and in all parts of the world. These crises not only occur too frequently, but also are too costly. Countries everywhere therefore have enacted laws that established regulatory authorities with responsibility to implement appropriate regulations and supervisory practices to promote healthy and stable banking systems. However, relatively recent information has become available that indicates that countries do not choose to regulate and supervise their banks in exactly the same way. Such information helps enable researchers to examine what regulations and supervisory practices work best. The results of these examinations can be extremely important to policy makers when considering changes to make in regulatory regimes in response to the most recent banking crisis.
Keywords: 330; bank regulations; banking crises; banking laws; banks; financial crises; supervisory practices; World Bank